FACTORS RELATED TO THE INCIDENT OF HYPERTENSION IN THE ELDERLY IN TEUPIN KUYUN VILLAGE, SEUNUDDON DISTRICT, NORTH ACEH DISTRICT, 2024 - Nelva Riza; Novi Susanti; Suryani Suryani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Hypertension can be defined as persistent blood pressure where the systolic pressure is above 120 mmHg and the diastolic pressure is above 90 mmHg. This study aims to determine the factors associated with the incidence of hypertension in the elderly in Teupin Kuyun Village, Seunuddon District, North Aceh Regency. This research design uses cross sectional. In determining the sample using the total sampling technique. The number of samples taken was 42 respondents. The variables studied were age, hereditary history, salt consumption. Hypertension data was obtained through blood pressure measurements, age and salt consumption data were obtained through questionnaires. This research uses statistical tests Chi-Square with p-value (< 0.05). Based on the research results, it was found that 40 people (95%) of elderly respondents had hypertension, based on tests Chi-Square value is obtained P=0.088, which means there is no significant relationship between age and the incidence of hypertension. In the hereditary variable, 30 people (71%) were found. There are offspring who have hypertension, based on tests Chi-Square value is obtained P=0.001, which means there is a significant relationship between heredity and the incidence of hypertension. In the salt consumption variable, 35 people (83%) found Those who consumed more salt experienced hypertension, according to tests Chi-Square value is obtained P=0.001, which means there is a significant relationship between salt consumption and the incidence of hypertension.